CULTURAL COMMUNICATION IN THE PRESERVATION OF TRADITIONAL BALINESE DANCE BY THE BALI ARTS INSTITUTE (LKB) SARASWATI IN BEKASI CITY - I Gede Aryadi Dharma; Yudhistira Ardi Poetra (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Bali is an area that has various types of traditional dance arts. Initially Balinese traditional dance was only based on worship and prayer, but now Balinese dance has developed into an art that is used as entertainment. The purpose of this research is to find out the cultural communication efforts of the Saraswati Bali Arts Institute (LKB) in preserving traditional Balinese dance in Bekasi City. This study uses a type of qualitative research. This study uses a descriptive qualitative research method. This research looks at the problem through a constructivism paradigm which seeks to explain a social phenomenon based on the views or experiences of the object under study. The results of this study show that LKB Saraswati has made efforts to preserve culture through organizing training at Pura Agung Tirta Bhuana Bekasi. In addition, LKB Saraswati relies on social media for documentation of training activities. LKB Saraswati also opens services for the needs of Balinese arts entertainment, such as wedding receptions using Balinese themes or concepts, opening of an event, or simply performing freelance dance at certain events or events. In addition, in this study it was found that there were communication barriers when carrying out conservation. Among them are frame of mind barriers and cultural barriers.